EXTERNALITIES OF KEDAI IPS ON ACADEMIC COMMUNITY SOCIAL SCIENCE STUDENT OF TARBIYAH AND TEACHER TRAINING FACULTY - Pusposari, Luthfiya Fathi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Social Science Education Department (PIPS) of Faculty Education and Teacher Training (FITK) five grades at C and D class 2016/2017 have pioneered the establishment of Kedai IPS. The purpose of establishing kedai IPS is to implement and getting practical experience of entrepreneurship subject that have been taught in the class. In the development Kedai IPS related to externality. Externality is the impact of activities that affected does not involve in that activities. It can be defined that the market failed to perform its function properly. The purpose of this article is to analyze the externalities generated by Kedai IPS Social science students of faculty education and teacher training. The approach used is descriptive qualitative. Data collected using interview and observation. The results show that there three externality of kedai IPS on Social science students of faculty education and teacher training. First externality positive consumer that are improving the quality of entrepreneurship learning in social science students, supporting the accreditation assessment program, consumer are more satisfy with the product consumed; Second externality producer positive is the existence of kedai IPS can increase welfare of social science community and the third Kedai IPS would bring effects of teaching and learning process in the classroom because it is located around in the class room.